129Xe NMR analysis reveals efficient gas transport between inborn micro-, meso- and macropores in geopolymers. (May 2022) - Li, Jing; Mailhiot, Sarah; Sreenivasan, Harisankar; Kantola, Anu M.; Telkki, Ville-Veikko; Kinnunen, Paivo
Abstract: Geopolymers are alumino-silicates with inborn mesoporous structures. For construction applications, the knowledge on the porous structure and fluid dynamics is important. In this work, the interconnected pore structures of metakaolin-based geopolymers and dynamics of guest molecules were studied by 129 Xe nuclear magnetic resonance (NMR), by exploiting the high sensitivity of the 129 Xe chemical shift to its local environment. The 129 Xe NMR spectra revealed three different pore structures experienced by xenon gas in the geopolymers: the first associated with microporous zeolite-analogous cages (≤2 nm), the second with the mesopores (2–50 nm) and the third with free Xe in larger voids. The sizes of mesopores, heat of adsorption as well as pore connectivity were determined as a function of water-to-solid ( w / s ) ratio. The results show that the pore structures can be tailored by changing the w / s ratio, providing tunability both for potential construction, catalysis, and adsorbent applications. Graphical abstract: Unlabelled Image